2020
DOI: 10.1002/uog.20401
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of predictive models for QUiPP App v.2: tool for predicting preterm birth in asymptomatic high‐risk women

Abstract: Objectives Accurate mid‐pregnancy prediction of spontaneous preterm birth (sPTB) is essential to ensure appropriate surveillance of high‐risk women. Advancing the QUiPP App prototype, QUiPP App v.2 aimed to provide individualized risk of delivery based on cervical length (CL), quantitative fetal fibronectin (qfFN) or both tests combined, taking into account further risk factors, such as multiple pregnancy. Here we report development of the QUiPP App v.2 predictive models for use in asymptomatic high‐risk women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 17 publications
(15 reference statements)
0
40
0
Order By: Relevance
“…In this paper, we report findings from the validation of the three algorithms appropriate for the cohorts with symptoms of TPTL. Development and validation of the predictive models for asymptomatic high‐risk women is reported in another paper by our group published in the same issue of the Journal.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we report findings from the validation of the three algorithms appropriate for the cohorts with symptoms of TPTL. Development and validation of the predictive models for asymptomatic high‐risk women is reported in another paper by our group published in the same issue of the Journal.…”
Section: Methodsmentioning
confidence: 99%
“…More recently cervical length measurement, quantitative fetal fibronectin and clinical factors have been combined and developed into a predictive model for preterm birth in asymptomatic women. This work has demonstrated that spontaneous preterm both can be accurately predicted with AUC values ranging from 0.75 to 0.90 40 . VOCs have potential benefits, in addition to the existing published model for several reasons.…”
Section: Discussionmentioning
confidence: 87%
“…They only had 15 cases of spontaneous preterm birth <34 weeks. In our most recent validation of the fetal fibronectin (fFN) QUiPP asymptomatic algorithm, 86 cases (out of 1081 women) from multiple sites illustrated close correlation between predicted and actual event rates …”
Section: Disclosure Of Interestsmentioning
confidence: 99%
“…The QUiPP app, a decision‐making tool for preterm birth, is an accurate determinant of preterm birth risk as proven in evaluating outcomes of nearly 3000 high‐risk women from multiple sites . Fundamentally, QUiPP's core value is to individualise risk and facilitate shared decision‐making.…”
Section: Disclosure Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation